Developing a digital learning environment team-based project to support online learning in Indonesia - Rahmat Fadhli; Aris Suharyadi; Fery Muhamad Firdaus; Meilina Bustari (Institute of Advanced Engineering and Science, 2023)
The purpose of this study is to describe the process of developing learning tools to support a team-based digital learning environment (DLE) project in library management courses. The analyze, design, develop, implement, and evaluate (ADDIE) development model is used in this study to investigate this type of research and development (R&D). The study included 162 students from four universities in Indonesia. Data is gathered through media and material validation questionnaires, learning management system (LMS) user satisfaction questionnaires, and lesson learning outcomes tests. Instruments include media and material validation sheets, LMS user satisfaction instruments, and lesson learning outcomes test instrument sheets. The media validation test and material results show that all media can be used with minor adjustments. Students have responded positively to the DLE application for online learning at universities. Learning tools are critical for raising motivation and accomplishing course learning outcomes. In the future, the evolution of learning media may be accompanied by the evolution of learning designs. As a result, the learning process and learning outcomes can be optimized. This study makes recommendations for revamping learning materials, media, and design to increase student motivation to learn.